APLIKASI Brachionus plicatilis UNTUK KELANGSUNGAN HIDUP LARVA IKAN BANDENG Chanos chanos Forskal PADA KELOMPOK PERIKANAN USAHA BERSAMA KABUPATEN ACEH TIMUR - Jayanthi, Sri; Arico, Zulfan; Faisal, Teuku Muhammad (Universitas Muhammadiyah Tapanuli Selatan, 2022)
In seed cultivation business, feeding seeds is a critical component towards successful cultivation. The problems faced at this time are the low level of technology and knowledge possessed by farmers, both types of feed, supplementary feeding and water management, so that the growth rate and survival rate obtained in milkfish cultivation are still very low. For this reason, accurate information and training is needed regarding milkfish hatchery technology as a reference that can be used by milkfish farmers. Based on the problems faced by the Joint Business Fisheries Group partners and the results of the agreement between the University of Samudra Community Service Team and partners, solutions were obtained (1) socialization of the importance of natural fish feed, namely rotifers for the survival of milkfish, (2) training in culture techniques Rotifers (Brachionus plicatilis) as natural food for milkfish, (3) making ponds/ aeration tanks for culture Rotifers (Brachionus plicatilis) as natural food for milkfish. The method of implementing the activities includes four main stages, namely field surveys, socialization, training, and assistance to monitor and evaluate the progress of the results of activities for the sustainability of the program in the village. Activities that have been carried out include four main stages, namely field surveys, socialization of activities, training on natural food culture, rearing and harvesting of fish that will be carried out at the end of August, and assistance to monitor and evaluate the progress of the results of activities for the sustainability of the program in the Gampong Baroh Bugeng. So that there has been an increase in knowledge and skills about the importance of natural food in the form of Brachionus plicatilis in milkfish cultivation so that currently milkfish farmers increase milkfish yields, increase the quality and quantity of live seeds so they can increase milkfish production and yields and create ponds. Rotifera (Brachionus plicatilis) culture aeration tub as natural fish food.